Jaramillo, Samuel (2009), Hacia una teoría de la renta del suelo urbano, Bogotá, Universidad de los Andes, 445 p. - Duhau, Emilio (Estudios Demográficos y Urbanos, 2011)
Jaramillo, Samuel. (2009). Hacia una teoría de la renta del suelo urbano, Bogotá, Universidad de Los Andes.